2006
DOI: 10.1002/bit.21017
|View full text |Cite
|
Sign up to set email alerts
|

High-level production of amorpha-4,11-diene in a two-phase partitioning bioreactor of metabolically engineeredEscherichia coli

Abstract: Reconstructing synthetic metabolic pathways in microbes holds great promise for the production of pharmaceuticals in large-scale fermentations. By recreating biosynthetic pathways in bacteria, complex molecules traditionally harvested from scarce natural resources can be produced in microbial cultures. Here we report on a strain of Escherichia coli containing a heterologous, nine-gene biosynthetic pathway for the production of the terpene amorpha-4,11-diene, a precursor to the anti-malarial drug artemisinin. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
139
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 229 publications
(146 citation statements)
references
References 17 publications
6
139
0
1
Order By: Relevance
“…5, compound 1) was first described from Escherichia coli which had been engineered to express the mevalonate pathway from Saccharomyces cerevisiae and amorpha-4,11-diene synthase (ADS) from A. annua (8). Development of a two-phase partitioning bioreactor allowed production of 0.5 g∕L of amorpha-4,11-diene (9). Analysis of transcriptional responses and pathway metabolites showed that 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase limited production, leading to perturbation of fatty acid biosynthesis and generalized membrane stress (10,11).…”
mentioning
confidence: 99%
“…5, compound 1) was first described from Escherichia coli which had been engineered to express the mevalonate pathway from Saccharomyces cerevisiae and amorpha-4,11-diene synthase (ADS) from A. annua (8). Development of a two-phase partitioning bioreactor allowed production of 0.5 g∕L of amorpha-4,11-diene (9). Analysis of transcriptional responses and pathway metabolites showed that 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) reductase limited production, leading to perturbation of fatty acid biosynthesis and generalized membrane stress (10,11).…”
mentioning
confidence: 99%
“…To reduce the loss, the secreted amorphadiene was in situ captured in dodecane organic phase in a two-phase partitioning bioreactor. [97] In contrary to the case of amorphadiene, artemisinic acid precipitates in the fermentor. Therefore, isopropyl myristate oil was supplied for solubilizing the deposited artemisinic acid.…”
Section: Increasing Harvest Ratementioning
confidence: 98%
“…Expression of MEV pathway together with and Artemisia annua amorphadiene synthase produced 122 mg/L of amorphadiene. Production of amorphadiene was increased using a two-phased partitioning system which trapped over 97% of the amorphadiene produced in the organic phase resulting in a production of 480 mg/L of amorphadiene [31].…”
Section: Metabolic Engineering Of the Isoprenoid Biosynthetic Pathwaymentioning
confidence: 99%